2010
DOI: 10.1002/jez.b.21371
|View full text |Cite
|
Sign up to set email alerts
|

Skin wound healing in axolotls: a scarless process

Abstract: Urodele amphibians, such as the axolotl (Ambystoma mexicanum), have the unique faculty among vertebrates to regenerate lost appendages (limbs and tail) and other body parts (apex of the heart, forebrain and jaw) after amputation. Interestingly, axolotls never seem to form scar tissue at the site of amputation once regeneration is completed. Before now, very few studies were directly focused on the description of the events happening during wound healing after a skin injury in salamanders. In this paper, we dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
139
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(150 citation statements)
references
References 39 publications
9
139
2
Order By: Relevance
“…More recent studies in the axolotl reported the recruitment of neutrophils in deep tissue wounds but not in regenerating limbs (8,31). By contrast, using a range of methods, the present study confirms the active involvement of macrophages within the regenerating axolotl limb.…”
Section: Pbs-liposupporting
confidence: 74%
See 2 more Smart Citations
“…More recent studies in the axolotl reported the recruitment of neutrophils in deep tissue wounds but not in regenerating limbs (8,31). By contrast, using a range of methods, the present study confirms the active involvement of macrophages within the regenerating axolotl limb.…”
Section: Pbs-liposupporting
confidence: 74%
“…S9). α-Smooth muscle actin (α-SMA) is an established marker for differentiated myofibroblasts displaying subepithelial localization (31)(32)(33) in several species. Macrophage-depleted animals showed increased numbers of α-SMA-positive cells compared with the normally low levels observed in control animals at 20 dpa (Fig.…”
Section: Mononuclear Phagocytes Regulate Regenerative Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Chablais and Jazwinska (2012) did not look at p-Smad2 and they did not test Smad3-specific inhibitors, such as SIS3, to confirm that inhibition of heart regeneration was due solely to the loss of p-Smad3. In axolotl limb regeneration, scar formation is never observed (Levesque et al, 2007(Levesque et al, , 2010Denis et al, 2013). We observe low levels of p-Smad3 very early post-amputation (Figs 2 and 5).…”
Section: Discussionmentioning
confidence: 54%
“…3K,L). Axolotl tissue regeneration is a typically scar-free process that occurs with minimal collagen deposition (Levesque et al, 2010;Seifert et al, 2012), but extensive and aberrant collagen deposition was observed in the mesenchyme of mubritinib-treated limbs. The phenotype observed here after long-term ErbB2 inhibition indicates a disruption of these scar-preventing programs and resembles the phenotype observed in amputated limbs after total macrophage ablation (Godwin et al, 2013).…”
Section: Nrg1 Supplementation Rescues Regeneration In Denervated Limbsmentioning
confidence: 99%